Rom, Italien. Auf dem Weg zur Rekonstruktion eines mittelrepublikanischen Tempels. Die Forschungen von 2020 am Largo Argentina in Rom - Zink, Stephan; D'Angelo, Giulia; Ceci, Monica (e-Forschungsberichte des DAI, 2021)
Despite the challenges of the pandemic, the collaborative project at Largo Argentina in Rome was able to make a significant step forward towards the reconstruction of the Mid Republican phase of Temple A. Its extant remains, which are hidden in an artificial underground area, were documented in a 3D model (SfM). It provides the basis for analytical architectural drawings. Moreover, it was possible to launch the study of the architectural terracotta from the site. A review of the excavator’s archival documents, in conjunction with an examination of the material, allowed preliminary but promising results in identifying parts of the roof decoration of Temple A.